DEVELOPMENT AND COMPARATIVE EVALUATION OF THE EFFECTIVENESS OF A DIAGNOSTIC AND TREATMENT ALGORITHM FOR COMPLEX SURGICAL TREATMENT OF DIFFUSE TOXIC GOITER - Khamdamov, B.Z.; Khamroev, U.P. (JOURNAL OF EDUCATION AND SCIENTIFIC MEDICINE, 2022)
Background. Reducing the incidence of diffuse toxic goiter is one of the urgent problems of endocrine surgery. According to some authors, it reaches 48% of all thyroid diseases. Purpose. To develop and give a comparative assessment of the effectiveness of a therapeutic diagnostic algorithm for complex surgical treatment of diffuse toxic goiter. Methods. The clinical material consisted of 582 patients with diffuse toxic goiter, who were treated and examined at the Regional Multidisciplinary Clinic of the city of Bukhara from 2011 to 2021. The initial diag- nosis was necessarily carried out by an endocrinologist. Examination of patients was complex and includ- ed clinical, laboratory and instrumental research methods. Results. The results of surgical methods for the treatment of diffuse toxic goiter can sometimes be very disappointing. Intraoperative bleeding, especially from the remaining thyroid tissue, requiring repeated co- agulation does not always achieve the desired effect. Moreover, as clinical cases have shown, complica- tions of this kind are often the causes of other, no less dangerous types of complications that can affect both the immediate results of surgical treatment and long-term ones. Conclusion. The use of a complex surgical method of treatment based on the diagnostic and treatment algorithm developed by us in patients with diffuse toxic goiter made it possible, in comparison with the con- trol group of patients, to increase the number of good and satisfactory results of treatment by 11.6%, to reduce unsatisfactory results of treatment by 2, 7 times and avoid recurrence of thyrotoxicosis.